A survey of canine haemoprotozoan parasites from Turkey, including molecular evidence of an unnamed Babesia - Aktas, Munir; Ozubek, Sezayi (Elsevier Sci Ltd, 2017)
Canine tick-borne apicomplexan parasites have emerged in recent years, showing a wider geographic distribution and increased global prevalence. A reverse line blot assay was performed on 219 blood samples collected from domestic dogs for simultaneous detection of all named canine piroplasm species as well as Hepatozoon canis. Ten samples hybridized to the Theileria/Babesia and Babesia catch all probes but did not hybridize to any species-specific probe tested, suggesting the presence of an unrecognized Babesia species or genotype. Sequencing results showed 91.5%, 91.9%, 92.4%, 92.4%, and 89.2% similarity to B. canis, B. vogeli, B. rossi, B. gibsoni, and B. conradae, respectively. The highest homology (98.1-98.5%) observed was with unnamed Babesia sp. isolates (Ludhiana and Malbazar) described in dogs, Babesia sp. of buffalo origin, Babesia sp. Kashi 2, and Babesia orientalis, along with Babesia occultans of cattle origin. The partial cox1 sequence indicated that this isolate was most similar to Babesia sp. 1 HG-2012, with an identity of 86.5%. The survey revealed high prevalence of haemoprotozoans in domestic dogs (57.5%, CI 50.7-64.2), with Hepatozoon canis the most prevalent (54.3%, CI 47.5-61.117%), followed by Babesia sp. (4.6%, CI 2.2-8.2), B. vogeli (1.4%; CI 0.3-3.9), and B. canis (0.4%, CI 0-2.5). Combined infection of Hepatozoon canis and Babesia sp. was detected in five (2.3%, CI 0.7-5.2) samples and of H. canis and B. vogeli in two (0.9%, CI 0.1-3.2) dogs. The study contributes insight into the distribution and phylogenetic diversity of canine piroplasms in Turkey.
Keywords: Babesia canis; Babesia vogeli; Babesia sp; Dog; Hepatozoon canis; RLB